Modalities of Post-Rhinoplasty Edema and Ecchymosis Measurement: A Systematic Review. Issue 2 (May 2022) - Levin, Marc; Ziai, Hedyeh; Roskies, Michael
Background: Post-rhinoplasty edema and ecchymosis can influence patient satisfaction with surgery as well as result in poor quality of life. Methods to quantify such edema and ecchymosis have been described in the literature. Despite this, there is currently no collective understanding of which methods are the most effective. Hence, this systematic review aims to describe and analyze the literature on post-rhinoplasty edema and ecchymosis measurement techniques. Methods: Standard bibliographic databases (OVID Medline, EMBASE, and PubMed) were searched from their inception to December 2019 for the terms: "rhinoplasty", "postoperative", "edema", and "ecchymosis". Descriptive analysis was completed. Results: The search revealed 1116 articles of which 33 met inclusion criteria and were included for qualitative synthesis. A total of 1801 patients from all studies were included. Of the 33 included studies, there were 57 unique ecchymosis/edema measurements. The majority of studies measured edema/ecchymosis on post-operative day 1, 2, 3 and 7. Ninety-three percent of measurements described were taken subjectively from a human rater. Other techniques described included magnetic resonance imaging, ultrasound, 3-dimensional imaging, and digital analysis. Less than half of the subjective ecchymosis/edema gradings were completed by a blinded rater. Conclusion: There are a wide variety of post-rhinoplasty edema and ecchymosis techniques being used by rhinoplasty surgeons. The majority of post-rhinoplasty edema and ecchymosis measurements are completed by unblinded subjective raters. It is important that facial plastic surgeons select an accurate measurement tool so they may be able to initiate precise patient-specific management of edema and ecchymosis.